They choose less, but do better: the paradoxical behavior of women in the engineering field (Praxis Educativa, 2024)
It analyzes the behavior of enrollment and academic performance of men and women in careers with low female presence. After creating a set of indexes of gender gaps and internal efficiency, a descriptive and longitudinal statistical analysis of academic registration databases of the programmatic offerings of a public university between 2014 and 2023 was performed. As a result, women apply less to engineering, but once they choose this option, they show a better academic performance. Although female enrollment has expanded, in areas such as engineering there is evidence of lags and gaps. It is women who show higher rates of retention, permanence, approval and timely graduation, in addition to presenting a significantly higher average performance. The argument of lower mathematical competencies of women to explain their professional choices in engineering is questioned. It highlights the importance of socio-educational interventions of attitudinal change that expand their choices to this área.
Keywords: stereotypes; higher education; engineering; gender equality; equal opportunity